Ancillary testing for diagnosis of brain death: a protocol for a systematic review and meta-analysis - Chassé, Michaël; Glen, Peter; Doyle, Mary-Anne; McIntyre, Lauralyn; English, Shane W; Knoll, Greg; Lizé, Jean-François; Shemie, Sam D; Martin, Claudio; Turgeon, Alexis F; Lauzier, François; Fergusson, Dean A (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background The essential clinical diagnostic components of brain death must include evidence for an established etiology capable of causing brain death, two independent clinical confirmations of the absence of all brainstem reflexes and an apnea test, and exclude confounders that can mimic brain death. Numerous confounders can render the clinical neurological determination of death (NDD) virtually impossible. As such, clinicians must rely on additional ancillary testing. Methods/design We will conduct a systematic review and a meta-analysis of ancillary testing for the neurological determination of death. The primary objective of this systematic review is to evaluate the accuracy of these ancillary tests compared to the three accepted reference standards: (1) clinical diagnosis, (2) four-vessel angiography and (3) radionuclide imaging. This objective will be investigated using two different populations with different baseline risks of brain death: comatose patients and patients with a neurological determination of death. We will search MEDLINE, EMBASE and the Cochrane Central databases for retrospective and prospective diagnostic test studies and interventional studies. We will report study characteristics and assess methodological quality using QUADAS-2, which is used to assess the quality of diagnostic tests. If pooling is appropriate, we will compute parameter estimates using a bivariate model to produce summary receiver operating curves, summary operating points (pooled sensitivity and specificity), and 95% confidence regions around the summary operating point. Clinical and methodological subgroup and sensitivity analyses will be performed to explore heterogeneity. Discussion The results of this project will provide a critical evidence base for the neurological determination of death. The results will help clinicians to select ancillary tests based on the best available evidence. Our systematic review will also identify the strengths and weaknesses in the current evidence for the use of ancillary tests in diagnosing brain death. It will serve as a foundation for further research and the development of prospective studies on currently used or novel techniques for NDD. Protocol registration PROSPERO Registration Number: CRD42013005907